Clonal Propagation of Coffea arabica with Indole Butyric Acid and Acclimatization Conditions in Amazonas, Peru - Chichipe Oyarce, Jardy (2021)
The use of hormones is important in improving the propagation process. The objective of the experiment was to identify the best dose of indole butyric acid (IBA) hormone for the rooting of coffee cuttings of the typical variety through clonal propagation in the Amazon region. The experiment was carried out in two stages. Both stages were carried out under a Completely Randomized Design (CRD). The percentage of rooting of cuttings and the number of roots were evaluated. The coffee tree clones were collected from rust tolerant elite plants. In the laboratory, the cuttings were immersed for 10 minutes in fungicide and then in five doses of IBA hormone (1000, 1500, 2000, 2500, and 3000 mg L−1) of IBA. They were then placed in a microtunnel. With the best dose obtained in stage 1 of IBA (T4: 2000 mg L−1), which achieved a rooting percentage of 52.50% and 5.8 roots on average, stage 2 was installed for the evaluation of acclimatization conditions (greenhouse and nursery). Thirty plants of the Típica variety were evaluated per treatment. Regarding the results after 90 days, the greenhouse obtained the highest values with 72.22% survival, a plant height of 9.48 cm, 4.32 mm stem diameter, 6.53 leaves per plant, 9.65 cm leaf length, and 3.83 cm leaf width. The IBA hormone in a controlled environment such as the greenhouse achieves good vegetative propagation for the Típica variety.